2004
DOI: 10.1523/jneurosci.3977-03.2004
|View full text |Cite
|
Sign up to set email alerts
|

EnhancedIn VitroMidbrain Dopamine Neuron Differentiation, Dopaminergic Function, Neurite Outgrowth, and 1-Methyl-4-Phenylpyridium Resistance in Mouse Embryonic Stem Cells Overexpressing Bcl-XL

Abstract: Embryonic stem (ES) cells provide a potentially unlimited source of specialized cells for regenerative medicine. The ease of inducing stable genetic modifications in ES cells allows for in vitro manipulations to enhance differentiation into specific cell types and to optimize in vivo function of differentiated progeny in animal models of disease. We have generated mouse ES cells that constitutively express Bcl-XL, an antiapoptotic protein of Bcl-2 family. In vitro differentiation of Bcl-XL overexpressing ES (B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
60
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(75 citation statements)
references
References 40 publications
13
60
0
Order By: Relevance
“…19,20 The analysis of the proliferation of neural precursor cells (Nestin þ -BrdU þ ), glia progenitor/precursor cells (GFAP þ -BrdU þ and vimentin þ -BrdU þ ), and neuronal progenitors (b-III-tubulin þ -BrdU þ ) showed: Firstly, the quantification of BrdU þ or Nestin þ cells confirmed the expected parallel temporal profile for both markers and Bcl-X L increased the numbers of stained cells during the whole of the differentiation period. These findings are consistent with results from studies using mES cells, 7 and bax-bak-deficient mice which displayed an increased pool of progenitor cells in the subventricular zone. 31 Second, quantification of double BrdU þ -Nestin þ cells indicated that most of the proliferating cells (BrdU þ ) were Nestin þ , while approximately one half of the Nestin þ cells incorporated BrdU.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…19,20 The analysis of the proliferation of neural precursor cells (Nestin þ -BrdU þ ), glia progenitor/precursor cells (GFAP þ -BrdU þ and vimentin þ -BrdU þ ), and neuronal progenitors (b-III-tubulin þ -BrdU þ ) showed: Firstly, the quantification of BrdU þ or Nestin þ cells confirmed the expected parallel temporal profile for both markers and Bcl-X L increased the numbers of stained cells during the whole of the differentiation period. These findings are consistent with results from studies using mES cells, 7 and bax-bak-deficient mice which displayed an increased pool of progenitor cells in the subventricular zone. 31 Second, quantification of double BrdU þ -Nestin þ cells indicated that most of the proliferating cells (BrdU þ ) were Nestin þ , while approximately one half of the Nestin þ cells incorporated BrdU.…”
Section: Discussionsupporting
confidence: 91%
“…In conclusion, in the context of hNSCs research, amounting data indicate that Bcl-X L plays a major role in modulating the generation of neurons from both rodent-and human-derived stem cells, [7][8][9][10] and present work. Here, we contribute data indicating a more general role of Bcl-X L , controlling the balance between the generation of neurons and glia from differentiating immortalized and non-immortalized hNSCs.…”
Section: Discussionsupporting
confidence: 53%
See 2 more Smart Citations
“…Generation of 6-hydroxydopamine-lesioned PD model rats and an amphetamine-induced rotation test were performed as described previously [24]. Adult rat SVZ NP cells under bFGF-proliferation were harvested 2 days after Nurr1 transduction and dissociated into single cells in CMF-HBSS as described above.…”
Section: In Vivo Transplantationmentioning
confidence: 99%